Characterisation of Pectobacterium carotovorum subsp. brasiliense isolates causing blackleg and soft rot diseases of potato in South Africa - Moleleki, Lucy N. (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.